2019
DOI: 10.1007/978-3-319-99516-8
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things From Hype to Reality

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 3 publications
0
42
0
9
Order By: Relevance
“…BC creates a trusted network among suppliers and eliminates the need for the middle man 6 ; secondly, another supplier in the chain can also track the product. Rayes and Salam 7 suggested that this makes them highly efficient with high transmission speed, reduces the cost, and enhances the quality significantly as compared with the traditional FSC.…”
Section: Introductionmentioning
confidence: 99%
“…BC creates a trusted network among suppliers and eliminates the need for the middle man 6 ; secondly, another supplier in the chain can also track the product. Rayes and Salam 7 suggested that this makes them highly efficient with high transmission speed, reduces the cost, and enhances the quality significantly as compared with the traditional FSC.…”
Section: Introductionmentioning
confidence: 99%
“…Although this tremendous evolution of IoT is being backed by new software, advances at a hardware level are still required. Thus, the demand for innovative multifunctional sensors in the near future is urgent, specifically sensors with new functionalities, and higher sensitivity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Communication devices utilize the Internet infrastructure and protocols to create a world of connected devices, like Wireless Sensor Networks (WSN) and Internet of Things (IoT). This technological advancement enables the progress of many technological and life processes bringing to us smart cities, autonomous vehicles, robotization and intelligent robot behavior [1,2,3,4]. In that context, information security has a very important role in compromising the integrity and privacy of data in such an integrated world can cause serious damage, even to the level of a general disaster [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%